Roblox top adventure games - Wiltshire, Alex; Jelley, Craig; Marsh, Ryan; Stuckey, John; Bolder, Joe (New York, NY Harper, an imprint of HarperCollinsPublishers, 2018)
Offers tips and tricks for more than forty adventures in Roblox, with interviews with the games' creators
"From the Bloxy Award-winning Jailbreak and Lumber Tycoon 2 to the massively popular Heroes of Robloxia and Apocalypse Rising, this action-packed book gives you the official scoop on some of the most popular and critically acclaimed adventure games on Roblox. Each profile tells you everything you need to know, including a guide to gameplay, interviews with the creators, and tips and tricks to take your skills to the next level." -- From Amazon.com
"A guide to over 40 awesome games"--Cover
1
Keywords: Roblox (Computing platform) -- Juvenile literature; Video games -- Design -- Juvenile literature; Internet games -- Design -- Juvenile literature; Roblox (Computing platform); Video games -- Design; Internet games -- Design; Roblox (Computing platform) -- Juvenile literature; Internet games -- Design -- Juvenile literature; Video games -- Design -- Juvenile literature; Roblox (Computing platform); Video games -- Design; Juvenile works; Illustrated works